Kajian Empiris: Hubungan Minat Belajar Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran Al Qur'an-Hadis - Uswatun Hasanah; Firman Mansir; Masni Erika Firmiana; Iredho Fani Reza; Harmathilda Harmathilda; Dini Permana Sari (CV. Era Digital Nusantara, 2026)
This research reveals that interest in learning has a significant correlation on student learning outcomes in al-Qur'an and Hadith subjects. Students with high interest in learning show a better level of activity and understanding in the learning process, while students with low interest tend to be passive and have difficulty achieving academic standards. Therefore, implementing learning methods that are interesting and actively involve students is very important to increase their interest and learning outcomes. This research involved 70 students with results showing that the average student interest in learning is in the good category, with a score of 82.80, which contributes positively to understanding the material. Apart from that, student learning outcomes also showed good improvement, with an average score of 83.16, reflecting that students not only have high interest, but are also able to achieve satisfactory achievements. The analysis shows that there is a significant and strong relationship between learning interest and student learning outcomes, with a correlation value of 0.788 with 62.1 % interest in learning to learning outcome. These findings confirm that increasing interest in learning contributes to improving learning outcomes. Therefore, educators need to apply interactive and interesting learning methods to increase student interest and learning outcomes.